Be Faithful to the Covenant: A Technical Translation of and Commentary on Malachi 2.10-16 - Ko, Ming Him (The Bible translator, 2014)
This article offers a technical and text-critical interpretation of Mal 2.10-16. This text is textually and syntactically difficult because of the ambiguity of the Hebrew that leads to the complexity of various textual judgments. This complexity further leads to contrasting views of whether the “covenant” refers to marriage or not. This article thus gives a detailed technical commentary on Mal 2.10-16, arguing that the “covenant” refers to both marriage and the covenant of the fathers.